Vestibular-Related Frontal Cortical Areas and Their Roles in Smooth-Pursuit Eye Movements: Representation of Neck Velocity, Neck-Vestibular Interactions, and Memory-Based Smooth-Pursuit - Fukushima, Kikuro; Fukushima, Junko; Warabi, Tateo (Frontiers in Neurology, 2011)
Smooth-pursuit eye movements are voluntary responses to small slow-moving objects in the fronto-parallel plane. They evolved in primates, who possess high-acuity foveae, to ensure clear vision about the moving target. The primate frontal cortex contains two smooth-pursuit related areas; the caudal part of the frontal eye fields (FEF) and the supplementary eye fields (SEF). Both areas receive vestibular inputs. We review functional differences between the two areas in smooth-pursuit. Most FEF pursuit neurons signal pursuit parameters such as eye velocity and gaze-velocity, and are involved in canceling the vestibulo-ocular reflex by linear addition of vestibular and smooth-pursuit responses. In contrast, gaze-velocity signals are rarely represented in the SEF. Most FEF pursuit neurons receive neck velocity inputs, while discharge modulation during pursuit and trunk-on-head rotation adds linearly. Linear addition also occurs between neck velocity responses and vestibular responses during head-on-trunk rotation in a task-dependent manner. During cross-axis pursuit–vestibular interactions, vestibular signals effectively initiate predictive pursuit eye movements. Most FEF pursuit neurons discharge during the interaction training after the onset of pursuit eye velocity, making their involvement unlikely in the initial stages of generating predictive pursuit. Comparison of representative signals in the two areas and the results of chemical inactivation during a memory-based smooth-pursuit task indicate they have different roles; the SEF plans smooth-pursuit including working memory of motion–direction, whereas the caudal FEF generates motor commands for pursuit eye movements. Patients with idiopathic Parkinson’s disease were asked to perform this task, since impaired smooth-pursuit and visual working memory deficit during cognitive tasks have been reported in most patients. Preliminary results suggested specific roles of the basal ganglia in memory-based smooth-pursuit.